2020
DOI: 10.3390/met10101296
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Grain Size Evolution with Different Approaches via FEM When Hard Machining of AISI 4140

Abstract: Thermo-mechanical loads during hard turning lead to the formation of so-called White Layers on the machined surface. Characterized by a very fine microstructure and high hardness, White Layers have a negative effect on the fatigue life of a component. The fundamental mechanism for the White Layer formation is the dynamic recrystallization (DRX). Therefore, in the current work, two different DRX models, Helmholtz free energy and Zener-Hollomon, are implemented into Abaqus/Explicit to predict the thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In this study, the critical temperature for onset of DRX is assumed to be 1213 K. The material constants in relation to DRX of γ grains of IN718 alloy were sourced from Geng et al [11,30]. X DRX is predicted according to an incremental form of the JMAK model that is activated by plastic strain expressed as [30,46]:…”
Section: Microstructural Model For Drx Of γ Grain During Lfwmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the critical temperature for onset of DRX is assumed to be 1213 K. The material constants in relation to DRX of γ grains of IN718 alloy were sourced from Geng et al [11,30]. X DRX is predicted according to an incremental form of the JMAK model that is activated by plastic strain expressed as [30,46]:…”
Section: Microstructural Model For Drx Of γ Grain During Lfwmentioning
confidence: 99%
“…where g c1 , g c2 , g c3 , g l1 , g l2 , and g l3 are material constants, ε < 0.1s −1 for low strain rate regimes, 0.1s −1 < ε < 10s −1 for medium strain rate regimes, and ε > 10s −1 for high strain rate regimes, and their values were taken from Geng et al [11]. The average grain size D ave was calculated by using a weighted average of the recrystallised grain size d DRX and non-recrystallised grain size D ave (t−1) as [46]: where (t) and (t − 1) are the current and previous computational time steps.…”
Section: Microstructural Model For Drx Of γ Grain During Lfwmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with grinding, dislocation density in WL after turning is usually higher, causing severely strained matrix [ 4 , 8 , 9 ]. Despite high temperatures and superimposing high stresses, the size of the carbides inside WL remains unchanged, whereas martensite matrix is refined down to several tens of nanometers [ 8 , 10 , 11 , 12 ]. Li et al [ 11 ] also reported the steep grain size gradient in the near surface region.…”
Section: Introductionmentioning
confidence: 99%